The regional cooperation-based warehouse location problem for relief supplies. (December 2016) - Chen, Yingzhen; Zhao, Qiuhong; Wang, Lei; Dessouky, Maged
Highlights: A regional cooperation-based relief location model considering territorial priority is constructed. A compensation mechanism is adopted to show cooperation in emergency management. It is shown regional cooperation can significantly reduce the maximum expected cost of any region. A case study of the relief warehouse location problem in Beijing is demonstrated. The usefulness of considering both territorial priority and regional cooperation is verified. Abstract: Regions often cooperate with each other in emergency rescue efforts, often times maintaining the principle of territorial priority. In this paper, a regional cooperation-based relief warehouse location model is constructed that takes into consideration the principle of territorial priority. The objective of the model is to minimize the maximum expected cost of any region. Problems of different size are tested in numerical experiments. Results show that regional cooperation can significantly reduce the maximum expected cost of any region. Then, a case study of the relief warehouse location problem in the Northern Beijing area is demonstrated for the storage of disinfectants to be used in case of large-scale flooding. The expected cost in the pre-disaster planning and the efficiency of the rescue efforts during the disaster are both taken into account. A suitable value of the upper limit for the transport time is obtained. The work of this study verifies the usefulness of considering both territorial priority and regional cooperation in emergency management.